Rapid Improvement in Neck Disability, Mobility, and Sleep Quality with Chronic Neck Pain Treated by Fu’s Subcutaneous Needling: A Randomized Control Study - Ching-Hsuan Huang; Lung-Hung Tsai; Mao-Feng Sun; Zhonghua Fu; Jian Sun; Li-Wei Chou (Pain Research and Management)
Background. Chronic neck pain is a common musculoskeletal disorder caused by overuse of neck and upper back muscles or poor posture, and it is commonly combined with a limited range of motion in the neck and shoulders. Most cases will recover within a few days; however, the symptoms often recur easily. Fu’s subcutaneous needling (FSN) is a new therapeutic approach used to treat patients with chronic neck pain. However, there is no solid evidence to support the effectiveness of FSN on chronic neck pain and disability. Methods. Participants (n = 60) with chronic neck pain for more than 2 months with pain intensity scored by visual analog scale (VAS) more than five were enrolled in this trial. Participants were equally randomized into the FSN or transcutaneous electrical nerve stimulation (TENS) group who received interventions once a day on day 1, day 2, and day 4. They were assessed by outcome measurements during pre- and post-treatment and followed up for 15 days. Results. The VAS was immediately reduced in the FSN and TENS groups and sustained for 15 days of follow-up (all P<0.001). The immediate effects were also observed as the pressure pain threshold increased in the FSN group on day 2 (P=0.006) and day 4 (P=0.023) after treatment, and tissue hardness decreased by FSN on day 1 and day 2 after treatment (both P<0.001). FSN and TENS treatment improved neck disability and mobility; moreover, FSN promoted participants to receive better sleep quality, as determined by PSQI assessment (P=0.030). TENS had no benefit on sleep quality. Conclusion. FSN was able to relieve pain and relax muscle tightness. Notably, FSN significantly improved neck disability and mobility and enhanced sleep quality. These findings demonstrated that FSN could be an effective alternative treatment option for patients with chronic neck pain. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT03605576, registered on July 30, 2018.